2013
DOI: 10.2298/mpns1304163m
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and use of dietary supplement among students of the University of Nis (Serbia)

Abstract: Health professionals and users of dietary supplements should be educated better on the use of these products in order to make the supplement use safe, controlled and rational.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 14 publications
8
6
1
Order By: Relevance
“…To the best of our knowledge, this was the first nationwide survey to study the prevalence of NS used by in Chinese college students, and the prevalence was consistent with surveys from other countries such as 43% in Malaysia [ 24 ] and around 50% in the United States [ 46 , 47 , 48 , 49 ], but notably higher than in Japan [ 28 ], United Arab Emirates [ 19 ], and Iran [ 45 ], and lower than in Australia [ 22 ] and Serbia [ 55 ]. In the current study, we found that medical students tended to prefer using NSs compared to students who studied other majors; this was also found in other surveys conducted with medical and pharmaceutical students [ 18 , 56 , 57 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…To the best of our knowledge, this was the first nationwide survey to study the prevalence of NS used by in Chinese college students, and the prevalence was consistent with surveys from other countries such as 43% in Malaysia [ 24 ] and around 50% in the United States [ 46 , 47 , 48 , 49 ], but notably higher than in Japan [ 28 ], United Arab Emirates [ 19 ], and Iran [ 45 ], and lower than in Australia [ 22 ] and Serbia [ 55 ]. In the current study, we found that medical students tended to prefer using NSs compared to students who studied other majors; this was also found in other surveys conducted with medical and pharmaceutical students [ 18 , 56 , 57 ].…”
Section: Discussionsupporting
confidence: 81%
“…Regarding the association between demographic characteristics and NS users, most of our findings were the same with previous studies [ 26 , 62 , 73 , 74 , 75 ]. Many previous literatures have shown that female, old and highly educated were more likely to use NSs [ 22 , 45 , 55 ]. In our study, the participants were all college students and the age range was not large, so there were no significant differences according to the age and education levels.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this research study have demonstrated that using DSs is widespread in the UAE, with 51.3% (95% CI: 47.3%-54.3%) of respondents stating that they had at some point used a DS. This is similar to the findings from the United States (52%), 30 the findings from Australia (56%) 31 and the findings of the Health and Nutrition Examination Survey (53%). [32][33][34] The results also indicated that, compared with other nationalities such as Iranians (36.3%), 35 Irish (23%), 36 Croatians (30.5%), 37 Jordanians (27.4%), 38 and Portuguese (16%) (Marques-Vidal), 39 UAE citizens utilized DSs at a greater rate; however, the UAE participants did not use DSs as much as those in Columbia (73%) 40 or Serbia (68.1%).…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence of dietary supplement use among studied university students was 30.5%, which is similar to results for students in Korea (31.3%) [ 18 ] and the Middle East (39%) [ 19 ] and to the results obtained by Sotoudeh et al [ 18 ] for students in Tehran (33%) [ 20 ]. However, the usage prevalence among our students is lower than the prevalence among American (52%) [ 21 ], Australian (56%) [ 22 ], and Serbian students (68.1%) [ 23 ] and higher than in Jordanian (27.4%) [ 24 ] and Portuguese students (16%) [ 25 ]. Medical sciences students (33.1%) were slightly higher users of dietary supplements than were nonmedical sciences students (28.8%), which is in accordance to similar studies [ 19 , 26 ].…”
Section: Discussionmentioning
confidence: 71%